Pendampingan Program Santun Lansia dan Peningkatan Kunjungan Posyandu Lansia di UPTD Puskesmas Kedungsari Kota Mojokerto - Sajidin, Muhammad; Andriyanto, Arief; Wicaksono, Arif (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of this community service activity is to provide guidance and increase visits to the elderly in Posyandu by implementing the Santun Lansia program. The elderly are expected to be able to improve their activeness in visiting the elderly Posyandu. The method of implementing assistance is the Community Based Research (CBR) method. The service took place from July 1 to August 30, 2024 at the UPTD Kedungsari Health Center, Mojokerto City, involving 103 elderly people. The results of community service are that the implementation of the Santun Elderly program can increase visits to the Elderly Posyandu at the UPTD Kedungsari Health Center, Mojokerto City. Elderly care needs to involve components to support the success of care such as family and health cadres, as well as health workers in health services. Health workers must be able to choose what methods and media to use when carrying out nursing interventions